Mechanisms of immune modulation in the tumor microenvironment and implications for targeted therapy - Czajka-Francuz, Paulina; Prendes, Maria J.; Mankan, Arun; Quintana, Ángela; Pabla, Sarabjot; Ramkissoon, Shakti; Jensen, Taylor J.; Peiró, Sandra; Severson, Eric A.; Achyut, Bhagelu R.; Vidal, Laura; Poelman, Martine; et al. (Frontiers in Oncology, 2023)
The efficacy of cancer therapies is limited to a great extent by immunosuppresive mechanisms within the tumor microenvironment (TME). Numerous immune escape mechanisms have been identified. These include not only processes associated with tumor, immune or stromal cells, but also humoral, metabolic, genetic and epigenetic factors within TME. The identification of immune escape mechanisms has enabled the development and implementation of therapies focused on boosting the immune response against cancers. Applications of latest scientific discoveries, including nanomedicines, immune checkpoint inhibitors, adoptive cell and epigenetic therapies can reprogram the TME and shift the host immune response towards promoting an antitumor effect. These approaches have translated into series of breakthroughs in cancer therapies, some of which have already been implemented in clinical practice. In the present article the authors provide an overview of some of the most important mechanisms of immunosuppression within the TME and the implications for targeted therapies against different cancers.